Language, literacy, and technology - Kern, Richard, 1956- (Cambridge : Cambridge University Press, 2015)
From the origins of writing to today's computer-mediated communication, material technologies shape how we read and write, how we construe and share knowledge, and ultimately how we understand ourselves in relation to the world. However, communication technologies are themselves designed in particular social and cultural contexts and their use is adapted in creative ways by individuals. In this book, Richard Kern explores how technology matters to language and the ways in which we use it. Kern reveals how material, social and individual resources interact in the design of textual meaning, and how that interaction plays out across contexts of communication, different situations of technological mediation, and different moments in time. Showing how people have adapted visual forms to various media as well as to social needs, this study culminates in five fundamental principles to guide language and literacy education in a period of rapid technological and social change.
Machine generated contents note: Introduction; Part I. Designing Meaning: 1. Communication by design; 2. Material resources: the medium matters; 3. Social ecologies; 4. The individual and design; Part II. Interactions of the Material, the Social, and the Individual: 5. Ancient writing in Mesopotamia; 6. Paper and print; 7. Writing redesigned: electronically mediated discourse; 8. Multimodal discourse; Part III. Educational Implications: 9. Principles and goals in language and literacy education; 10. Toward a relational pedagogy.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Language and languages -- Study and teaching -- Technological innovations; Language and languages -- Study and teaching -- Computer-assisted instruction; Literacy -- Study and teaching -- Computer-assisted instruction; Literacy -- Study and teaching -- Audio-visual aids; Education, Bilingual -- Teacher training